Review of eyeless Pseudosinella Schäffer (Collembola, entomobryidae, and lepidocyrtinae) from Brazilian caves - Cipola, Nikolas Gioia; Oliveira, João Victor L.C.; Bellini, Bruno Cavalcante; Ferreira, Aila Soares; Lima, Estevam C.Araújo De; Brito, Roniere A.; Stievano, Luis Carlos; Souza, Paolla G.C.; Zeppelini, Douglas (Insects, 2020)
Herein, eyeless Pseudosinella species from Brazilian caves are reviewed, including the description of 23 new species, new records plus additional notes on the descriptions of P. ambigua Zeppelini, Brito, and Lima and of P. guanhaensis Zeppelini, Brito, and Lima. We also provide an identification key to 27 eyeless species recorded from Brazil. To organize the 26 Brazilian eyeless taxa analyzed in this work, we organize them in apparently artificial groups: 11 species have one larger tooth on the unguiculus outer lamella (petterseni group); one presents unguiculus outer lamella smooth or serrated (never with a larger tooth), with 9 held prelabral chaetae undivided and the last 6 held prelabral chaetae bifurcated. The Brazilian species of eyeless Pseudosinella herein described present a remarkably conservate dorsal chaetotaxy; therefore, the main diagnostic characters are related to other features like prelabral, labral, and ventral head chaetotaxy and empodial complex morphology. In addition, our study suggests that Brazilian caves possibly shelter a great diversity of Pseudosinella taxa, several of them potentially cave dependent. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.
Keywords: Caves conservation; Idiochaetotaxy; New Species; Species group; Taxonomy; Troglofauna; Troglomorphism